Three new species of the genus Ambanus Ovtchinnikov, 1999 from China (Araneae: Amaurobiidae: Coelotinae) - Zhang, Zhi-Sheng; Zhu, Ming-Sheng; Song, Da-Xiang (Zootaxa, 2007)
Three new species of Ambanus Ovtchinnikov, 1999 (Araneae: Amaurobiidae: Coelotinae) from Mt. Changbai of Northeast China are described: A. pseudonariceus spec. nov., A. triangulatus spec. nov. and A. trisaccatus spec. nov. The study showed that all three new Ambanus species have five to six trichobothria on the retrolateral cymbium, similar to some Coelotinae from the Himalayan region. Draconarius kayasanensis (Paik, 1972) comb. nov. is transferred from Ambanus, and Ambanus nariceus (Zhu & Wang, 1994) comb. nov. from Coelotes.